INDIVIDUAL VALUES DAN PSYCHOLOGICAL WELL-BEING TERHADAP KOMITMEN ORGANISASI - Mubarok, Fikri (TAZKIYA JOURNAL OF PSYCHOLOGY, 2019)
AbstractThis research was conducted to determine internal factors in individuals that influence organizational commitment. This study uses a quantitative approach with multiple regression analysis. A sample of 171 nurses at Cempaka Putih Hospital was taken using a non-probability sampling technique. In this study, the authors modified the instrument, namely the Organizational Commitment Questionnaire (OCQ), Portrait Values Questionnaire (PVQ), and Psychological Well-Being Scale (PWBS). The instrument was tested for its validity using the confirmatory factor analysis (CFA) technique. The results showed that there were individual values and psychological well-being influences on organizational commitment. Self-acceptance and purpose in life have an influence on organizational commitment. Affective commitment dimensions are influenced by self-acceptance. The normative commitment dimension is influenced by positive relations with others, purpose in life, personal growth, and tradition. The continuance commitment dimension is influenced by purpose in life and hedonism. The researcher hopes that the results of this study can be developed in future studies. besides, the researchers hope that further research will be conducted in the context of work other than nurses.AbstrakPenelitian ini dilakukan untuk mengetahui faktor-faktor internal pada individu yang mempengaruhi komitmen organisasi. Penelitian ini menggunakan pendekatan kuantitatif dengan analisis multiple regression analysis. Sampel berjumlah 171 perawat di RSIJ Cempaka Putih yang diambil dengan teknik non-probability sampling. Dalam penelitian ini, penulis memodifikasi instrumen, yaitu Organizational Commitment Questionnaire (OCQ), Portrait Values Questionnaire (PVQ), dan Psychological Well-Being Scale (PWBS). Instrumen di uji terlebih dahulu validitasnya menggunakan teknik confirmatory factor analysis (CFA). Hasil penelitian menunjukkan bahwa ada pengaruh individual values dan psychological well-being terhadap komitmen organisasi. Self acceptance dan purpose in life memiliki pengaruh terhadap komitmen organisasi. Dimensi affective commitment dipengaruhi oleh self acceptance.  Dimensi normative commitment dipengaruhi oleh positive relation with others, purpose in life, personal growth, dan tradition. Dimensi continuance commitment dipengaruhi oleh purpose in life dan hedonism. Peneliti berharap bahwa hasil penelitian ini dapat dikembangkan pada penelitian selanjutnya. selain itu peneliti berharap penelitian selanjutnya dilakukan pada konteks pekerjaan selain perawat.